Ion channel gene GJB2 influences the intercellular communication by Up-regulating the SPP1 signaling pathway identified by the single-cell RNA sequencing in lung adenocarcinoma - Liu, Zuo; Xiao, Zengtuan; Wang, Xiaofei; Zhang, Lianmin; Zhang, Zhenfa (Frontiers in Oncology, 2023)
Objective: Firstly, observe the prognostic significance and the biological functional effects of gap junction protein beta 2 (GJB2 or Cx26) in lung adenocarcinoma (LUAD). Subsequently, explore the role played by GJB2 in intercellular communication by single-cell RNA sequencing. Method: We made a differential analysis of GJB2 expression through public databases and investigated the clinical characteristics and prognostic significance. ESTIMATE analysis and Tumor Immune Estimation Resource (TIMER) database were utilized to illustrate the association of GJB2 with immune infiltration and components of the tumor microenvironment. Gene Ontology (GO), Kyoto encyclopedia of genes and genomes (KEGG), and Gene set enrichment analysis (GSEA) were performed to study the biological function of GJB2. Cell-cell communication was analyzed using the CellChat R package through sc-RNA data. Results: GJB2 has an outstanding prognosis value in LUAD and a close relationship was found between GJB2 and immune infiltration in LUAD. GJB2 could participate in several tumor biological processes, including extracellular matrix remodeling and upregulation of multiple cancer-related active pathways. GJB2 related hub-genes influence intercellular communication through the SPP1 signaling pathway. Conclusion: Our study illustrates one mechanism by which GJB2 exerts its cancer-specific relevant effects, that is, causing changes in intercellular communication through the SPP1 signaling pathway. Blockade of this pathway may limit the functional role of GJB2 and provide us with promising new perceptions for LUAD treatment.